Impact of post- transplant diabetes on left ventricular function following heart transplantation. (4th February 2022) - Borgenvik, S; Jumatate, R; Giesdal, G; Werther Evaldsson, A; Braun, O; Smith, JG; Radegran, G; Meurling, C; Ingvarsson, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Orthotopic heart transplantation (OHT) is a standard treatment option for end-stage heart failure (HF). Although post-transplant diabetes (PTDM) is a main complication due to immunosuppressive corticosteroid treatment, its impact on left ventricular (LV) function following OHT has not been described. Purpose: The purpose of this study was to analyse the possible effect of PTDM on LV function in OHT patients using conventional and speckle tracking echocardiography. Furthermore, this study aimed to compare echocardiographic LV function parameters to clinical parameters, including heart rate, blood pressure, and Hemoglobin A1C (HbA1c) in OHT recipients with or without PTDM. Methods: We performed a retrospective study including 77 (59 males) OHT patients (PTDM n = 29) using data from the routine 3-year follow-up. The mean age of the study population was 52 ± 14 years. All patients were examined using 2-dimensional transthoracic echocardiography with an ultrasound system equipped with a S5-1 transducer. Systolic-, diastolic blood pressure, heart rate, and HbA1c levels were recorded in conjunction with the TTE examination for each participant. Results: Participants with PTDM had impaired LV function measured by global longitudinal strain (LVGLS), increased septum diameter, and a lower diastolic EA-ratio compared to the non- PTDM patients. Additionally, a significant correlation between high HbA1c levels and poor LVGLS was detected.  Conclusion: We found that subtle LV dysfunction, including remodeling of the heart (i.e., increased wall thickness), reduced longitudinal contractile function, and altered diastolic function, was present in OHT patients with PTDM. Our findings suggest that sub-clinical myocardial dysfunction in OHT patients with PTDM is progressive and may evolve to clinical LV dysfunction and HF. Hence, analyzing secondary cardiac effects of PTDM in OHT patients have a therapeutic and prognostic value and may influence long-term patient survival.